Sirtuin 1: A Dilemma in Transplantation - Sara Assadiasl; Nuala Mooney; Bahareh Mohebbi; Yousef Fatahi; Narjes Soleimanifar (Journal of Transplantation)
Sirtuin 1, a member of sirtuin family of histone deacetylase enzymes, has been implicated in a variety of physiologic and pathologic events, including energy metabolism, cell survival, and age-related alterations. In view of the anti-inflammatory properties of sirtuin 1 along with its protective role in ischemia reperfusion injury, it might be considered as contributing to the promotion of transplantation outcome. However, the potential ability of sirtuin 1 to induce malignancies raises some concerns about its overexpression in clinic. Moreover, despite the findings of sirtuin 1 implication in thymic tolerance induction and T regulatory (Treg) cells survival, there is also evidence for its involvement in Treg suppression and in T helper 17 cells differentiation. The identification of sirtuin 1 natural and synthetic activators leads to the proposal of sirtuin 1 as an eligible target for clinical interventions in transplantation. All positive and negative consequences of sirtuin 1 overactivation/overexpression in the allograft should therefore be studied thoroughly. Herein, we summarize previous findings concerning direct and indirect influences of sirtuin 1 manipulation on transplantation.